Political Socialization Strategy in Increasing Voter Participation in the 2020 Regional Head Election in Sidoarjo Regency: Strategi Sosialisasi Politik Dalam Meningkatkan Partisipasi Pemilih Pada Pemilihan Kepala Daerah Tahun 2020 Kabupaten Sidoarjo - Raul, Mohammad Ayub Akbar; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2021)
The Sidoarjo Regional General Election Commission has the task and function of organizing general elections in the Sidoarjo Regency area. However, in reality, community participation, especially those who have the right to vote, have not fully exercised their right to vote. The socialization carried out by the Sidoarjo Regional General Election Commission was not optimal due to the pandemic and the less optimal method of socialization carried out by the Sidoarjo General Election Commission in this case the mural art (graffiti) competition. The Sidoarjo Regional General Election Commission must have a strategy in increasing voter participation in the 2020 Sidoarjo Regional Head Election. The purpose of this study is to determine the strategy of the Sidoarjo Regional General Election Commission. The method in this research is descriptive qualitative. With the informant of the commissioner of the community participation division as a key informant. Data collection techniques were carried out through interviews, field observations, and documentation. Data analysis was carried out through Miles and Hubberman data analysis which consisted of data collection, data presentation, data reduction and conclusions. The results of the research on the strategy of the Sidoarjo General Election Commission in increasing participation in the 2020 Sidoarjo Regional Head election, namely the political socialization strategy with face-to-face socialization and socialization through the media, including socialization innovations through mural art media.